Invasive Species : Introduction Pathways, Economic Impact, and Possible Management Options - El-Shafie, Hamadttu; El-Shafie, Hamadttu (IntechOpen, 2020)
Invasive alien species (IAS) are a menace to agricultural crops and ornamental plants worldwide due to climate change and global warming. They vector serious human and animal diseases and endanger biological diversity through competition and niche displacement. This book addresses issues pertaining to introduction pathways of invasive species, their bionomics, dispersal, risk assessment, economic impact, and possible management and control options. It provides comprehensive information on global invasion, economic impact, and management options for the red palm weevil, spotted wing Drosophila, and the South American tomato pinworm. Additionally, it examines the economic utilization of invasive plant species from the families Asteraceae and Cactaceae as means of management. University teachers and researchers in the fields of entomology, ecology, and environment, as well as students, will find this book useful.
English
Keywords: Regional geography; Biogeography